ANALISIS KASUS TENTANG JUAL BELI TANAH WARISAN YAN BELUM DIBAGI (STUDI PUTUSAN MAHKAMAH SYAR’IYAH SIGLI NOMOR: 291/PDT-G/2013/MS-SGI) - MAULANA RIALZI RIALZI (PREMISE LAW JURNAL, 2016)
The result shows that in the Islamic law, inheritance land which has not been distributed is prohibited to be bought and sold because it is still owned by the other heirs. If all heirs approve of the buy and sell, it can be bought and sold, otherwise it is considered illegal and revoked. Legal protection for the buyer of undistributed inheritance land is that he can file a complaint in civil case on the seller and the Notary/PPAT (official who is empowered to draw up deeds) who has drawn up the sales agreement. He can also file a complaint in criminal case by reporting a fraud as it is stipulated in Article 378 of the Criminal Code. Judge’s legal consideration in the Ruling of the Sharia Court No. 291/Pdt.G/ 2013/Ms-Sgl has fulfilled the sense of justice for the land owner since all heirs have had their equal share on the land so that they are not harmed Keywords: Buy and Sell, Inheritance Land